PENGENDALIAN PERSEDIAAN MENGGUNAKAN SIMULASI BERBASIS SPREADSHEET (Studi Kasus: Jaringan Toko Sepatu Olahraga) - Syaeful Arief; Taufiq Aji (Kaunia: Integration and Interconnection Islam and Science, 2013)
A sports shoe store retail business whose sales are closely related to the ongoing trend when it. On the other hand, intense market competition and meet the market's appetite to add complexity and uncertainty that led to inventory planning are probabilistic. Demand variability, lead time is uncertain, and suppliers who require the purchase of serially into the challenges faced by retail sports shoes. To make decisions in situations such supplies can be used simulation approach. This study presents a spreadsheet-based simulation approach to resolve montecarlo inventory decisions. Spreadsheet application aids chosen because commonly used in a variety of companies. Simulation model was built by using Visual Basic for Application to perform computational mode. Simulation aims to (1) determine the time and the number of reservations that a minimum total inventory cost, (2) to decrease inventory costs against corporation existing condition. Computational results are executed to achieve steady state is able to provide a reduction in total inventory costs significantly.